Synthesis and Characterization of Novel 1, 4‐Di(o‐thioaryl)benzene Buta‐1, 3‐diynes. Issue 25 (2nd July 2018) - Kang, Master. Yongqiang; Guo, Yujing; Shi, Heping; Ye, Master. Shanshan; Zhang, Bianxiang
Abstract: The dimers of terminal alkynes were synthesized through a room temperature reaction which used (diacetoxyiodo)benzene as oxidizing agent and acetonitrile as solvent. The structures were characterized by 1 H NMR, 13 C NMR. The electrochemical and spectrochemical properties of the compounds were also characterized by cyclic voltammetry and UV spectroscopy. Meanwhile, the single crystal X‐ray analysis of the model compound was discussed.Introduction of the thioaryl group in ortho position lead to the red shift of the UV absorption peaks, and the introduction of a large steric hindrance group reduced the influences of the intermolecular π‐π interactions on their electronic properties. Moreover the sulfur atom can form the stable S−Au bond with gold. These data indicated that compounds3 b ‐3 d are expected to be applied in the field of molecular wires. Abstract : The dimers of terminal alkynes were synthesized using (diacetoxyiodo)benzene as oxidizing agent in acetonitrile for 30 min at room temperature in good to high yields. Due to the introduction of the thioaryl group in ortho position leading to the red shift of the UV absorption peaks, and to give a large steric hindrance group which avails to reduce the influences of the intermolecular π‐π interactions on their electronic properties. Moreover the sulfur atom can form the stable S−Au bound with gold.